Services Trade in Developing Asia: A Case Study of the Banking and Insurance Sector in Nepal - Dilli Raj Khanal (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
This study reviews the development of the banking and insurance sectors in Nepal and the effect of reforms and commitments linked to these sectors since the 1980s, when financial sector liberalization in Nepal began with deregulation of the interest rate structure and opening of the banking sector to foreign investors.
Keywords: F1; 330; Service Trade; Nepal